Analysis of Environmental Aspects and Impacts as Reference for Planning Environmental Management System Programs in The Upstream Oil and Gas Industry (Case Study: “X” Area on P Company) - Bima Ilham Rubiono; Mas Agus Mardyanto (Journal Research of Social Science, Economics, and Management, 2026)
Upstream oil and gas industry activities have complex operational characteristics and the potential to generate various significant environmental aspects and impacts. Activities such as drilling, fluid processing, and waste management can affect the quality of water, air, soil, and ecosystems surrounding operational areas. Therefore, a systematic approach is required to identify and evaluate environmental aspects and impacts as a basis for planning effective and sustainable environmental management system (EMS) programs that comply with applicable environmental regulations. This study aimed to analyze environmental aspects and impacts associated with upstream oil and gas operations and formulate priority EMS programs through risk assessment and multi-criteria decision analysis. The methods used included interviews, field observations using questionnaires and checklists, and literature reviews. Data were analyzed descriptively and analytically to identify environmental aspects and impacts based on company policies and applicable regulations, followed by risk assessment using the State-Owned Enterprises risk matrix to determine risk levels. The Analytical Hierarchy Process (AHP) method was also applied to prioritize proposed environmental program plans. The results indicated that P Company’s operational activities involved significant environmental aspects, including air emissions, liquid waste generation, hazardous waste management, noise emissions, potential oil spills, soil and water quality degradation, and contributions to greenhouse gas emissions. Based on the risk assessment results, several activities were categorized as having moderate to high risk levels, particularly those related to hydrocarbon spills and hazardous waste management. The risk controls implemented by the company were effective in reducing environmental risk levels to moderate and low categories.